Formulação e aplicação de metabólitos produzidos por Fusarium fujikuroi com ação bioherbicida - Todero, Izelmar (2021)
The present work aimed to evaluate the herbicide effect of the metabolites produced by Fusarium fujikuroi applied in pre and post-emergence in bioindicator plants and weeds, as well as to formulate a bioproduct. The experiments were divided into two stages, where in the 1st stage the potential of the fungus Fusarium fujikuroi for the production of exopolysaccharides (EPS), their concentration and the relationship of EPS with the bioherbicidal activity were evaluated. For this purpose, production in crude fermented broth and different methods of concentration (membranes, lyophilization and evaporation) were evaluated. The quantification was carried out using acid precipitation and the tests were carried out on Cucumis sativus leaves. In the 2nd stage, firstly, pre-emergence tests were carried out on Cucumis sativus, Bidens pilosa and Amaranthus retroflexus. At this time, seed imbibition and α-amylase activities were evaluated. In the formulation of the experiments, two different tests were carried out in order to investigate the interaction of the fermented broth without Fusarium fujikuroi cells with the adjuvants. Firstly, preliminary tests were carried out evaluating different concentrations of palm oil, Span® 80 and Tween® 80, Silweet L-77, Assist, Orgânico, Aureo and Nimbus. From the results, the two best formulations with two best commercial adjuvants (Silweet L-77 and Aureo) were selected and tests carried out on Bidens pilosa. The results obtained in the 1st stage of the thesis demonstrate that the fungus Fusarium fujikuroi can be considered a good exopolysaccharides producer. The technologies used to concentrate EPS proved to be efficient processes, with emphasis on lyophilization, followed by membranes and evaporation. The results indicate that when EPS concentrations increase, an increase in bioherbicide activity and a decrease in surface tension are obtained. When investigating different concentrations of palm oil, Span® 80 and Tween® 80 with different levels of Hydrophilic-Lipophilic Balance (HLB), the treatment that showed the best result was a mixture of Tween® 80, palm oil and crude broth. Testing the different commercial adjuvants Silwet L-77 + Tween® 80 + crude broth, these showed greater damage to the weed. In the germination of Cucumis sativus, promising results were obtained. The evaluation in Bidens pilosa and Amaranthus retroflexus demonstrated that there is a herbicide effect in the crude broth, for both weed species. In relation to the percentage of germination by imbibition of the seeds, it progressively increased with the imbibition time. All concentrations of Fusarium fujikuroi broth tested showed inhibition of seed imbibition. The effect of α-amylase activity varies with each treatment. Testing the different commercial adjuvants, Silwet L-77 showed greater compatibility with the crude broth, leading to irreversible damage.